Case Report: Laryngospasm as Initial Manifestation of Amyotrophic Lateral Sclerosis in a Long-Survival Patient With Heterozygous p.D90A – SOD1 Mutation - Capece, Giuliana; Ceroni, Mauro; Alfonsi, Enrico; Palmieri, Ilaria; Cereda, Cristina; Diamanti, Luca (Frontiers in Neurology, 2021)
Amyotrophic Lateral Sclerosis (ALS) is a fatal neurodegenerative disease affecting motor neurons. Although its etiology is still unknown, many genes have been found to be implicated in ALS pathogenesis. The Cu/Zn superoxide dismutase (SOD1) gene was the first to be identified. Currently, more than 230 mutations in the SOD1 gene have been reported. p.D90A (p. Asp90Ala) is the most common SOD1 mutation worldwide. It shows both autosomal and recessive inheritance in different populations. To date, five Italian patients with the heterozygous p.D90A mutation have been reported. None of them complained of laryngological symptoms as the initial manifestation of ALS, although they had atypical clinical features. We describe a long-survival patient carrying heterozygous p.D90A mutation who presented with severe laryngospasm due to bilateral vocal cord paralysis. We suggest that genetic analysis may help to diagnose ALS with insidious onset like hoarseness, laryngospasm, and other type of voice disturbances.